Cetopirus complanatus (Cirripedia: Coronulidae) from the late Middle Pleistocene human settlement of Pinnacle Point 13B (Mossel Bay, South Africa) - Collareta, Alberto; Marean, Curtis W.; Jerardino, Antonieta; Bosselaers, Mark (Zootaxa, 2017)
The late Middle Pleistocene cave site of Pinnacle Point 13B (PP13B, South Africa) has provided the archaeologically oldest evidences yet known of human consumption of marine resources. Among the marine invertebrates recognised at PP13B, an isolated whale barnacle compartment was tentatively determined as Coronula diadema and regarded as indirect evidence of human consumption of a baleen whale (likely Megaptera novaeangliae). In this paper we redetermine this coronulid specimen as Cetopirus complanatus. This record significantly extends the fossil history of C. complanatus back by about 150 ky, thus partially bridging the occurrence of Cetopirus fragilis in the early Pleistocene to the latest Quaternary record of C. complanatus. Since C. complanatus is currently known as a highly specific phoront of right whales (Eubalaena spp.), we propose that the late Middle Pleistocene human groups that inhabited PP13B fed on a stranded southern right whale. Therefore, the whale barnacle from PP13B suggests the persistence of a southern right whale population off South Africa during the predominantly glacial MIS 6, thus evoking the continuity of cetacean migrations and antitropical distribution during that global cold phase. Interestingly, the most ancient evidence of humans feeding on a whale involves Eubalaena, historically the most exploited cetacean genus, and currently still seriously threatened with extinction due to human impact.